IOT based library book searching system Using RFID - Shaikh, Nazmin A (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 3 No 2 (2019): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
Library has many connotations. A library is a assembly of properties, information and facilities which is prepared for use, and maintained by an institution, a public body, or a private individual. In the more traditional sense, it means a collection of books. Typically we need a librarian to pick the books and hand it over to the person to whom the books are being issued. This might be an easy task incase the library floor area is small, but this could be really hectic job if the library area is very large. We need to search for the for books that requires a lot of time, to automate this process of book finding and picking we suggest a system that is an mechanical system which is IOT based. This system will consist of two sections. In first section the computer will consist of database of all library books along with the the RFID code. And in the second section there will be an RFID reader which will scan the RFID tags on the shelf and when the book is detected there will be a output(LED blinking at that point/beep sound near the book etc). There is also a provision for the library members that in their smart phone there will be an application that will only have access for the library members. The user can check the availability of a particular book by title or author name using his mobile phone. This application will show the availability or non availability of particular book they are searching for or the day when it will be available etc. This can be done remotely. So as to save your time. And the devices will be IOT based. This will ensure an easy search for books in the library. How to cite this article: Shaikh NA. IoT Based Library Book Searching System using RFID. J Adv Res Appl Arti Intel Neural Netw 2019; 2(2): 21-23